The Effect of BMI on Strengthening Exercise to Improve The Functional Ability of Knee Osteoarthritis: Pengaruh BMI terhadap Latihan Penguatan untuk Meningkatkan Kemampuan Fungsional pada Osteoarthritis Lutut - Narulicha, Desi Nadya; Ariyanto, Andry (Annual Physiotherapy Scientific Meeting Proceeding, 2023)
Background: Osteoarthritis is a degenerative joint disease that can get worse over time. It can also cause reactive changes to the cartilage edges of the knee joint. One of the contributing factors is the body mass index. For obese people, this poses a high risk because body weight puts a strain on the joints, especially the knee joints. Aim: This study aims to determine the effect of BMI on strengthening exercise to increase the functional ability of knee osteoarthritis. Research Method Experimental This research was conducted through a two-group pre-test post-test design with a sample size for group I of normal BMI totaling 12 people and group II for overweight BMI totaling 12 people. The two groups were given strengthening exercise for 4 weeks with a frequency of 2 times a week. The functional abilities of the two groups were measured using the WOMAC Index. Result: Based on the results of the paired sample t-test hypothesis testing in groups I and II, the value was (p <0.05) p = 0.000, which means that there is an effect of BMI on strengthening exercise to increase the functional ability of knee osteoarthritis. Conclusion: There is an effect of BMI on giving strengthening exercise to increase functional ability in knee osteoarthritis. Suggestion: Future researchers are expected to be able to control activities that affect sample activity.